Diffusion‐thermo effect on convective MHD flow of Cu‐water nanofluid including ramped wall temperature, velocity and concentration. Issue 3 (24th December 2022) - Gohain, Dipunja; Ahmed, Nazibuddin
Abstract: An unsteady convective MHD flow of water based Cu‐nanofluid past an impulsively started infinite vertical plate embedded in porous medium including ramped velocity, temperature and concentration in the existence of diffusion‐thermo effect, radiation and chemical reaction has been investigated. The non‐dimensional domain equations are computed by adopting Laplace transform technique. The impact of various pertinent parameters that are associated with the fluid velocity, temperature, concentration and moreover on skin friction coefficient, Nusselt number and Sherwood number has been represented graphically. It is figured out that, increase of Dufour effect causes to rise in both the momentum and temperature boundary layer. Further, it is ascertained that increase in the volume fraction of nanoparticles causes fall of velocity whereas it increases temperature together with the rate of heat transfer at the walls. Abstract : An unsteady convective MHD flow of water based Cu‐nanofluid past an impulsively started infinite vertical plate embedded in porous medium including ramped velocity, temperature and concentration in the existence of diffusion‐thermo effect, radiation and chemical reaction has been investigated. The non‐dimensional domain equations are computed by adopting Laplace transform technique. The impact of various pertinent parameters that are associated with the fluid velocity, temperature, concentration and moreover on skin friction coefficient, Nusselt number and Sherwood number has been represented graphically.…